Strategic Human Resource Management and Employment Relations - Malik, Ashish (Springer, 2018)
The theoretical roots for the study of human resource management (HRM) in organisations have existed in the Western contexts for over a century when seminal ideas of influential management thinkers such as Taylor, Drucker and McGregor were in prevalence. Earlier conceptualisations of work and employment adopted a different (pluralist) emphases and focused on terms such as labour welfare, labour relations, personnel management and industrial relations to name a few. One could argue, this view reflected contemporary developments in the field of HRM, albeit with different ideological and philosophical focus that have been in operation for several centuries. For example, in India, work practices were influenced by the ancient ideas of Chanakya (also referred to as Kautilya), whose pioneering work on Arthashastra was regarded as a treatise in the field of economics, politics, military strategy and governance. This seminal work had also developed ideas of organisation and administration in the fourth century BC. Indeed, one only needs to turn back and look at the practices of one of the world’s oldest multinational corporation–the erstwhile East India Company, which was founded in the early 1600 in India by the British to pursue trade with the East Indies. Even though it ended up trading, in the main, in the Indian subcontinent, its operations spanned across several borders. Managing people in the colonial era was quite different from how we manage people today. Some might even ask, has the nature of capitalism or business goals changed in principle? If so, what might have caused the change? Were these changes triggered by changes in people’s aspirations of seeking better and humane conditions of work and employment? Or, due to changing political agendas, new legislation for protecting workers, change in ideologies and other influences such as religion and industrial revolution? These questions bring to our mind the importance of changes in context and its distinctive and highly variable character. While the immediate focus of HRM and employment relations (ER) is on managing people and work within an agreed framework of the employer–employee relationship and setting the rules for engaging people and governing their conditions of employment, HRM and ER is also influenced by multiple, direct and indirect factors. These include a range of factors such as different: stakeholders state, regulation, customers and institutions. It is by learning the multiple and specific instances from different contexts that we may be able to generate some generic guidelines for understanding how we manage people and work.
An International Perspective